The Effect of Using Citrus Wood Charcoal in Broiler Rations on the Performance of Broilers - Baha Eddin Abu Bakr (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This study was conducted to investigate the effect of feeding citrus wood charcoal on the performance, feed intake and feed conversion efficiency of broiler chicks. A total of 120 broilers of Habbard strain at 22 days of age were used in the experiment and were divided into four groups of 30 birds in each. Each group was divided into five replicates with six chicks per replicate. Birds in the experimental groups were fed citrus wood charcoal at rates of 0, 2,4 and 8% of the ration DM in replacement of yellow corn. The results showed that inclusion of citrus wood charcoal at rate of 2% had an effect on body weight gain, feed intake and feed conversion efficiency. The results indicated that the effect of citrus charcoal is an age dependent as it had no effect at ages of more than 29 days. However, inclusion of citrus wood charcoal increased birds abdomen fat.